2019
DOI: 10.1590/1678-7757-2018-0420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic and Nd: Yag laser activation on irrigants on the push-out bond strength of fiber post to the root canal

Abstract: Objective: This in vitro study aimed to compare the efficacy of irrigants using various irrigation activation methods to the push-out bond strengths of fiber post to root canal luted with self-adhesive resin cement (SARC). Methodology: Forty-eight decoronated human canines were used. The specimens were divided into four groups corresponding with the post-space irrigation process and were treated as follows: distilled water (DW) (Control) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Some studies have shown better cleaning of the root canal walls when ultrasonic and Nd: YAG activation was performed, mainly in association with chelating solutions ( 23 , 24 ). On the other hand, some authors did not observe an improvement in the removal of the smear layer and debris when active irrigation was performed ( 22 , 25 ). This study evaluated only the chemical effect promoted by the chelating solutions, and it did not include another variable such as PUI or Nd: YAG laser.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have shown better cleaning of the root canal walls when ultrasonic and Nd: YAG activation was performed, mainly in association with chelating solutions ( 23 , 24 ). On the other hand, some authors did not observe an improvement in the removal of the smear layer and debris when active irrigation was performed ( 22 , 25 ). This study evaluated only the chemical effect promoted by the chelating solutions, and it did not include another variable such as PUI or Nd: YAG laser.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, there are reports of studies which aimed to evaluate the effect of active irrigation using ultrasound and neodymium: yttrium-aluminum-garnet (Nd: YAG) laser to remove the smear layer and debris after post-space preparation ( 7 , 22 ). Some studies have shown better cleaning of the root canal walls when ultrasonic and Nd: YAG activation was performed, mainly in association with chelating solutions ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are attributed to the variable densities of dentin, technical sensitivity, difficult application of adhesive into the narrow post space, and limitations in light curing of the root canal system. Some studies have reported a reduction in bond strength from the coronal towards the apical region (Fundao glu Küçükekenci & Küçükekenci, 2019;Jowkar et al, 2020). However, in this study, the bond strength in all groups was slightly, but not significantly, higher in the middle third compared with the coronal third of the roots.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the push‐out bond strength in megapascals (MPa), the debonding force in Newtons (N) was divided by the cross‐sectional area using the formula P=F/A where A is the post‐dentin surface area, which was calculated using the formula below: sans-serifAgoodbreak=π0.25em()sans-serifRgoodbreak+sans-serifrsans-serifh2+()sans-serifRgoodbreak−sans-serifrsans-serif20.5 In this formula, R indicates the coronal root canal radius, r indicates the apical root canal radius, and h indicates the thickness of each section. (Fundaoğlu Küçükekenci & Küçükekenci, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…3 Among the various chemical irrigants used in dentistry, sodium hypochlorite (NaOCl) had gained widespread popularity due to its antimicrobial effectiveness, tissue dissolving properties, and lubrication. 4 It also possesses low viscosity which allows easy introduction and penetration into the canal space along with adequate shelf life and cost-effectiveness. 5 However, existing literature advocates that NaOCl is unable to remove the inorganic component of the smear layer which barricades adhesion of bonded restorations.…”
Section: Introductionmentioning
confidence: 99%